Proceedings Ninth IEEE International Conference on Computer Vision 2003
DOI: 10.1109/iccv.2003.1238648
|View full text |Cite
|
Sign up to set email alerts
|

Paracatadioptric camera calibration using lines

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Based on their unified model (see Section 3.1.5), they showed that from two respectively three images of lines, one may fully calibrate a central hyper-catadioptric respectively para-catadioptric camera. They gave an algorithm for the para-catadioptric case; Barreto and Araújo developed an algorithm for hyper-catadioptric cameras [28,31] as well as an improved algorithm for para-catadioptric ones that is able to fully compute the mirror shape [30,32]. Ying and Hu, Vandeportaele et al, and Wu et al gave similar algorithms [518,537,551].…”
Section: Lines -The Plumb-line Approachmentioning
confidence: 99%
“…Based on their unified model (see Section 3.1.5), they showed that from two respectively three images of lines, one may fully calibrate a central hyper-catadioptric respectively para-catadioptric camera. They gave an algorithm for the para-catadioptric case; Barreto and Araújo developed an algorithm for hyper-catadioptric cameras [28,31] as well as an improved algorithm for para-catadioptric ones that is able to fully compute the mirror shape [30,32]. Ying and Hu, Vandeportaele et al, and Wu et al gave similar algorithms [518,537,551].…”
Section: Lines -The Plumb-line Approachmentioning
confidence: 99%
“…This fact is explored in [21] in order to calibrate the sensor using the image of lines. A similar approach can be applied for the estimation of lens distortion.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, a conic X 0 is the paracatadioptric image of a line if, and only if, it goes through the circular points and satisfies R 0T X 0 T 0 = 0. This result has been used in [21,22] in order to constrain the search space and accurately estimate line projections in the paracatadioptric image plane.…”
Section: Line Projection In Paracatadioptric Camerasmentioning
confidence: 99%
“…This is a common problem as well in perspective vision [7], [6] as in omnidirectional vision [8], [9], [10]. Marchand et al [6] proposed a virtual visual servoing (VVS) based perspective camera calibration.…”
Section: A Overwiewmentioning
confidence: 99%